The Effect of Flavonoids of Phaleria macrocarpa Fruit Extract on Aortic Diameter Mice Menopause Model - Khoirinda, Ani; Fadilah, R. A. Rahmawati Nurul; Sutrisno, Sutrisno; Irwanto, Yahya; Dewi, R. A. Rose Khasana (JURNAL INFO KESEHATAN, 2024)
Menopause is a phase experienced by women with an age range of 45-55 years. Menopause is a condition where menstruation stops for a minimum of 12 consecutive months due to the decline in ovarian function, leading to a reduction in estrogen levels. A decrease in estrogen can lead to impaired fat metabolism resulting in atherosclerosis. This study aimed to illustrate the influence of flavonoid extract derived from Phaleria Macrocarpa on the enlargement of the aorta's diameter of mice with a menopause condition. The method of this study is a genuine experimental laboratory setting with a research design of a Randomized Post Test Only Control Group setting. Using 32 female mice divided into 6 groups: K- (without ovariectomy and flavonoid extract Phaleria Macrocarpa), K + (ovariectomy without treatment), P1 (ovariectomy + dose 3.75 mg/mice/day), P2 (ovariectomy + dose 7.5 mg/mice/day), P3 (ovariectomy + dose 11.25 mg/mice/day), and P4 (ovariectomy + dose 15 mg/mice/day). Administration of flavonoid extract Phaleria Macrocarpa was carried out for 14 days. Data analysis using statistical analysis. The results showed that in a post-hoc test, namely the administration of Phaleria macrocarpa flavonoid extract at a dose of 11.25 mg/mice/day and 15 mg/mice/day showed that it could increase the dilation of the aortic diameter of mice model menopause. The study concludes that the flavonoid fruit extract from Phaleria Macrocarpa has the ability to increase the width of the aorta in mice with a menopause condition. In future studies, it is recommended to investigate various variables in order to identify the factors that contribute to the narrowing of the aorta. Additionally, it is suggested to perform further research specifically focusing on women going through menopause.